Situational Leadership, Organizational Climate, and Teacher Commitment as Determinants of Teacher Performance: A Systematic Literature Study in the Context of State Senior High Schools in Probolinggo City - Ullyl Danik Karyani; Ali Imron; Teguh Triwiyanto (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to analyze the influence of the principal's situational leadership style, organizational climate, and teacher commitment on teacher performance in public senior high schools in Probolinggo City. The background of this study is based on the importance of principal leadership in creating a conducive work environment and motivating teachers to improve the quality of learning. The method used is a Systematic Literature Review (SLR) through a survey of teachers from four public senior high schools in Probolinggo City. This study involved the entire population of 353 teachers, using a simple random sampling technique using the Slovin formula. The data collection instrument was a Likert-scale questionnaire that had been tested for validity and reliability. The research results show that the principal's situational leadership style has a positive and significant effect on teacher performance. A conducive organizational climate and high teacher commitment also significantly contribute to improved teacher performance. Furthermore, teacher commitment acts as a mediating variable, strengthening the relationship between leadership style and organizational climate on teacher performance.